Adsorption study of electric arc furnace slag for the removal of manganese from solution - Beh, Chin Lai; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw; Kamarudzaman, Mohd Zakwan; Abdan, Khalina (Science Publications, 2010)
Problem statement: Steel making slag from Electric Arc Furnace (EAF) is an abundant by- product in Malaysia steel making industry. It has potential to be used for heavy metal removal from contaminated water or waste water. Approach: The aim of this study was to investigate the characteristic and behavior of manganese removal by using EAF slag for efficient metal removal. The removal characteristics of manganese were investigated in term of sorption kinetics and isotherm. The batch adsorption kinetics and isotherm studies were carried out at 28°C and ten grams of EAF slag was added into 1 L manganese solution of various concentrations of 10, 25, 50, 75, 100 and 120 mg L-1. All these different mixtures were stirred and sampled at various desired times and centrifuged. The supernatant solutions were then collected for chemical analysis. Results: It was found that the EAF slag adsorption kinetics can be described well by the pseudo-2nd order kinetic model with fairly high correlation coefficients. The adsorption process obeyed the Langmuir isotherm model and the maximum uptake of the manganese from the solution is 2.31 mg L-1 g-1 of EAF slag used. Conclusion: From the study, it was concluded that the EAF slag can be an efficient adsorbent to remove manganese from both the solution and waste water.